Coal permeability evolution characteristics: Analysis under different loading conditions. Issue 2 (27th February 2020) - Guo, Haijun; Cheng, Zhixiang; Wang, Kai; Qu, Baolin; Yuan, Liang; Xu, Chao
Abstract: The drainage and utilization of coalbed methane (CBM) resources can not only ensure the safe production of coal mines but also can reduce greenhouse gas emissions and protect the environment. Coal permeability is the key factor that affects the CBM drainage efficiency. To understand the coal permeability evolution characteristics, coal specimens reconstituted by coal powder with different particle sizes were prepared and their permeability under loading conditions was investigated. The results indicate that the coal permeability evolution laws measured by different gases are completely different under constant hydrostatic pressure conditions due to the influence of effective stress and the coal matrix sorption‐induced deformation. Under constant effective stress conditions, the helium permeability of coals is almost unchanged if the effects of the Biot's coefficient of coals are ignored, but the methane permeability of coals decreases with increasing gas pressure. In the complete stress–strain process, the variation of coal permeability as the axial strain increases at different stages is almost completely different and the coal permeability in the residual plastic flow stage increases by 2.4–71 times, 1.5–39 times, and 2.8–116 times that of the initial state under the different boundary conditions. Furthermore, it is also found that the coal permeability evolution laws are determined by the effective stress, the sorption‐induced deformation of coal matrices, and the malconformation of gas adsorption in coals. This study can help us better understand the seepage characteristics of gas in coals and guide the CBM development. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd.